Common Reasons for Permanent Tooth Extraction and Its Correlation with Demographical Factors in Kabul, Afghanistan - Fayaz Y; Ahmadi NA; Ahmadi SU; Atiq MA (Dove Medical Press, 2024)
Yahya Fayaz,1 Naseer Ahmad Ahmadi,1 Shahab Uddin Ahmadi,1 Mohammad Asif Atiq2 1Department of Stomatology, Khatam Al Nabieen University, Kabul, Afghanistan; 2Department of Clinical Pharmacology, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Mohammad Asif Atiq, Department of Clinical Pharmacology, Kabul University of Medical Sciences, Kabul, Afghanistan, Tel +93777378141, Email masifatiq@gmail.comObjective: The aim of this survey was to investigate the main reasons for extraction of permanent teeth, and its correlation with age, gender, education level, smoking habits, and time of last dental visit, family income, and professions in Kabul, Afghanistan.Subjects and Methods: The study proposal was approved by Research Ethics Committee of Khatam AL Nabieen and was conducted over a period of 5 months; its population consisted 594 patients, aged 10- 70 years, who underwent extraction. The frequency distribution was calculated using X2 test, ANOVA and t-test for differences in mean number of patients.Results: A total of 594 patients underwent extraction. The highest rate (53.8%) of extraction occurred for those 21- 40 years old. Females compromised 51.3% of patients. Two hundred (33.6%) patients were uneducated. Tooth loss due to caries was 30.1%; patient-request was 18.3%; impacted teeth was 14.4%. Other causes were periodontal reasons, failed root canal therapy (RCT), Tooth mobility, and Root fractures.Conclusion: The result of this survey indicated that caries, patient request, and impaction were the leading reasons for tooth extraction. The majority of patients were uneducated, and had insufficient family income. Most of the patients were housewives and laborers.Keywords: Tooth Extraction, Dental Caries, Periodontal Disease